Mitigasi Gas Rumah Kaca Sektor Limbah pada Rumah Tangga - Seri Ulina Purba (Poltekkes Kemenkes Semarang, 2026)
Greenhouse gas (GHG) emissions from the household waste sector in Medan City show an increasing trend and are an important contributor to the city's total emissions, in line with the national increase. This problem is not only caused by limited infrastructure but is more influenced by people's behavior in waste management, as explained in the framework of Lawrence Green's theory (Precede-Proceed Model), which includes predisposition, enabling, and reinforcing factors. This study aims to analyze the relationship between knowledge, attitudes, availability of facilities, availability of waste bins, and willingness to sort waste with GHG mitigation in the waste sector. The method used was a quantitative survey with a cross-sectional design of 270 households in Medan City using the two-stage cluster sampling technique. Data was collected through interview questionnaires and analyzed categorically based on median, then tested using Chi-square (α=0.05). The results showed that knowledge, attitude, and willingness to sort waste had a significant relationship with GHG mitigation behavior (PR 4.84–4.95; p=0.0001). On the other hand, the availability of facilities and garbage cans was not significantly related (p>0.05). These findings confirm the dominance of psychosocial factors over physical means factors. In conclusion, efforts to mitigate GHG in the waste sector need to be focused on increasing knowledge, forming positive attitudes, and encouraging waste sorting behavior.